Teachers' perceptions of visual arts creativity practices in elementary schools in Indonesia: a study of aesthetic habitus - Probosiwi Probosiwi; Kirana Prama Dewi; Kopasz Tamás; Desiana Muryasari; Dian Effendi; Anggun Asmorojati (Institut Seni Indonesia Surakarta, 2025)
The background comes from the teaching practice experience of students in the elementary school education program, which mainly focuses on core subjects. Although the visual arts are not considered a core subject in elementary schools, they still play an important role in helping students grow and develop by raising awareness about artistic practices. The goal of this article is to explain what teachers think about creativity in visual arts learning during their teaching practices, as seen through the perspective of students in the school teacher education department. The study uses a qualitative approach. To collect data, the researchers conducted interviews, made observations, and reviewed documents. The data was analyzed using the Miles & Huberman method, and the results were presented in both written and table formats. The findings show that teaching practices in elementary schools, done by students in the education program, give them hands-on experience as future teachers. They use aesthetic ideas as a way to connect art and beauty in daily life. The students create art that fits their home environments. Also, aesthetics are included in habitus practices, which are internalized as structured ways of seeing, judging, feeling, and acting towards the subjects they study.